(untitled) (Modern Problems of Metallurgy, 2025)
The previous article presents the results of mathematical modeling and research using the developed models of the effect of the amount of lump additives introduced into a ladle bath (with a capacity of 250 t) during steel processing in a ladle furnace unit (LFU) on its hydrodynamic state. Using the example of using lump ferromanganese grade FMn78, taking into account different specific amounts of the additive (0,2; 1; 2; 3 kg/t), a significant effect of the studied factor on the hydrodynamics of the metal melt during the considered period (up to 4.5 s) of the ferroalloy additive being in the bath is shown. This work contains the results of a study of the effect of the additive amount on the thermal state of the metal melt under LFU processing conditions. The presented material is a logical continuation of previous studies, in which the initial conditions specified in the previous article are preserved. The work included two stages of research. At the first stage, the influence of the intensity of blowing of the metal bath in the ladle on its thermal state was estimated and experimentally assessed. An influence (from ≈0.08 ºС to ≈0.13 ºС depending on the intensity of blowing) on the thermal state of the bath in the considered period of time was determined. At the second stage, a mathematical model was developed and numerical studies were carried out on a computer program for its implementation, taking into account the above amounts of additives under conditions close to industrial ones. Based on the research results and the example of the cartogram given in the article, the zones of local changes in metal temperature at different points in time from the moment of introducing the additive into the melt are shown. The influence of the factor under consideration is confirmed on the given dependence of the change in melt temperature on the specific gravity of the introduced additive, taking into account the bath blowing modes. Taking into account the research results, a proportional decrease in the temperature of the metal melt in the contact zone of the additive inside the bath after its introduction is shown.